Assessment of Environmental Hazardous of Construction and Demolition Recycled Materials (C&DRM) from Laboratory and Field Leaching Tests Application in Road Pavement Layers. (2016) - Roque, A.J.; Martins, I.M.; Freire, A.C.; Neves, J.M.; Antunes, M.L.
Abstract: A research project aiming to contribute to the sustainable implementation of recycling of Construction and Demolition Waste (C&DW) in road pavements is ongoing. The use of Construction and Demolition Recycled Materials (C&DRM) in road pavements is envisaged as a solution with major environmental and economic benefits. Their application as unbound granular material in pavement layers (base, sub-base and capping layers) also has the advantage to allow the incorporation of large amounts of this type of materials, even coming from different sources. Engineering and environmental performance of these materials are being assessed through laboratory tests and field tests. The evaluation of the environmental hazardous of C&DRM is based in their leachability from compliance (batch test) and basic characterisation (column test and lysimeter test) leach tests. The results already obtained in leaching tests are presented and discussed in the paper. In case of compliance leach test, the results are compared with leaching limit values defined in the Portuguese legislation for waste acceptable at landfills for inert waste.